On the Distribution Functions of the Range and Quasi-range for the Extended Type I Generalized Logistic Distribution - Olapade, A. K. (2014)
In this paper, we obtain the distribution functions of the range and the quasi-range of the random variables arising from the extended type I generalized logistic distribution.